2017
DOI: 10.16943/ptinsa/2017/48949
|View full text |Cite
|
Sign up to set email alerts
|

Paleoclimatic Signals from the Proxy Records of the Southern Ocean: A Review

Abstract: Antarctic sea-ice extent and oceanic frontal systems are of primary importance to the marine biota since their marked meridional gradients in physical and chemical properties strongly regulate the phytoplankton contribution to primary productivity.Antarctic sea ice extent along with the Southern Ocean (SO) biological productivity varied considerably during glacial-interglacial periods, and both are known to have played a considerable role in regulating atmospheric CO 2 variations in the past. In the present re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Study of diatoms from surface sediments of Enderby Basin of Indian Sector of Southern Ocean revealed that the diatom abundance correlates well with the variation in Antarctic summer and winter sea-ice extent (Mohan et al, 2011). An interesting application of the morphology of diatom as a proxy is to analyze if and how it varied over glacial to interglacial transitions at the Polar Front, as this may reflect millennial-scale shifts in the position of this front, and the associated high export of biogenic silica (Shukla et al, 2013;Nair et al, 2015;Nair et al, 2017). Shukla et al (2013) suggested that variations in circum-polar upwelling were the main controlling factor in opal production during the last ~20,000 years.…”
Section: Late Quaternary Oceanic Changes In the Indian Sector Of The mentioning
confidence: 99%
“…Study of diatoms from surface sediments of Enderby Basin of Indian Sector of Southern Ocean revealed that the diatom abundance correlates well with the variation in Antarctic summer and winter sea-ice extent (Mohan et al, 2011). An interesting application of the morphology of diatom as a proxy is to analyze if and how it varied over glacial to interglacial transitions at the Polar Front, as this may reflect millennial-scale shifts in the position of this front, and the associated high export of biogenic silica (Shukla et al, 2013;Nair et al, 2015;Nair et al, 2017). Shukla et al (2013) suggested that variations in circum-polar upwelling were the main controlling factor in opal production during the last ~20,000 years.…”
Section: Late Quaternary Oceanic Changes In the Indian Sector Of The mentioning
confidence: 99%